CaCO3 as a new member of high solar‐reflective filler on the cooling property in polymer composites. Issue 2 (31st August 2020) - Tao, Yiyi; Mao, Zepeng; Yang, Zhangbin; Zhang, Jun
Abstract: Calcium carbonate (CaCO3 ) is the most commonly used inorganic filler in polymer materials to improve the mechanical properties and reduce the costs. However, there are few reports on the preparation of cooling materials using CaCO3 . In this study, CaCO3 was introduced into the polymer matrix as a solar reflective filler to prepare passive cooling materials. Specifically, the influences of CaCO3 content on the structure and performances of polyvinyl chloride (PVC)/CaCO3 composite films were characterized by scanning electron microscope (SEM), contact angle test, surface roughness and glossiness, solar reflectivity, thermal emissivity, temperature test and mechanical property characterization. When the volume fraction of CaCO3 reaches 67%, the total solar reflectance of PVC/CaCO3 composite films is 80.8%, which is 351.4% higher than that of PVC films. CaCO3 powder has little influence on the thermal emissivity of the atmospheric window (3‐5 μm and 8‐13 μm) of the composite films, which remains at a high level about 0.86. In temperature test, the final temperature of sample 67 v% is only 26.8°C, which is only 2.8°C higher than the room temperature and 22.2°C lower than that of PVC films. For comparison, the cooling performance of PVC/titanium dioxide (TiO2 ) composite films with 10 v% TiO2 was also measured, and the final temperature is 29.1°C, even 2.3°C higher than that of PVC/CaCO3 composite films with 67 v% CaCO3 . In this study, the cost‐effective and solar‐reflective PVC/CaCO3 composites have potential application in cooling material field. Abstract :